2023
DOI: 10.1111/nep.14137
|View full text |Cite
|
Sign up to set email alerts
|

Gender and socioeconomic disparities in global burden of chronic kidney disease due to glomerulonephritis: A global analysis

Abstract: Aim: To investigate the gender and socioeconomic disparities in the global burden of chronic kidney disease (CKD) due to glomerulonephritis from 1990 to 2019.Methods: Data were extracted from the global burden of diseases (GBD) 2019 study, including incidence, prevalence and disability-adjusted life-years (DALYs). Estimated annual percentage changes (EAPCs) were calculated to quantify the temporal trends in age-standardized rate (ASR) of CKD due to glomerulonephritis. Paired t-test, paired Wilcoxon signed-rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We further conducted the analysis on several risk factors for FSGS recurrence in children. The summary of the articles included in this study did not find the effect of gender on the recurrence of FSGS, and most studies also believed that gender would not affect the recurrence of FSGS 18,22,32 . What is more, the published study demonstrated that younger recipient age was found to be the most reliable predictors of recurrence of FSGS 18,25,33 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We further conducted the analysis on several risk factors for FSGS recurrence in children. The summary of the articles included in this study did not find the effect of gender on the recurrence of FSGS, and most studies also believed that gender would not affect the recurrence of FSGS 18,22,32 . What is more, the published study demonstrated that younger recipient age was found to be the most reliable predictors of recurrence of FSGS 18,25,33 .…”
Section: Discussionmentioning
confidence: 71%
“…The summary of the articles included in this study did not find the effect of gender on the recurrence of FSGS, and most studies also believed that gender would not affect the recurrence of FSGS. 18,22,32 What is more, the published study demonstrated that younger recipient age was found to be the most reliable predictors of recurrence of FSGS. 18,25,33 However, patients in another study who were older at the time of transplantation had a greater recurrence rate.…”
Section: Discussionmentioning
confidence: 94%
“…Gender-specific risk factors may differ because of different lifestyles or sex differences in pathophysiology. In some studies, men had a higher burden of hypertension, obesity, or dietary sodium than females [ 75 , 111 ]. Smoking appears to be a risk factor for hyperkalemia only in men [ 112 ].…”
Section: Improving Outcomes For Women With Ckd and Cvdmentioning
confidence: 99%
“…The increasing prevalence of chronic kidney disease (CKD) is a signi cant public health concern, involving about 10% of the global population [1], 1 exceeding the number of cases observed in diabetes, chronic obstructive pulmonary disease, and depressive disorders. [2][3][4] Individuals with a family history of high cholesterol are predisposed to develop CKD, implicating the composition of circulating lipoproteins, particularly the lipid and protein components, in CKD development. 5 Furthermore, lipids and their metabolites are essential constituents of cell and organelle membranes, signaling molecules, and energy generators, in uencing structural and functional aspects 6 .…”
Section: Introductionmentioning
confidence: 99%